Cyclin-Dependent Kinase 12 (CDK12), Human Kinase Domain; A Target Enabling Package - Bullock, A (University of Oxford, 2018)
A description of the materials and methods is included within the TEP datasheet. Cyclin-dependent kinase 12 (CDK12) phosphorylates RNA Pol II C-terminal domain (CTD) to promote transcriptional elongation of large DNA damage response genes. CDK12 is frequently mutated or amplified in cancer and its loss sensitises cells to DNA damage. Here we present 3 crystal structures of the human CDK12/CycK complex including apo, AMP-PNP and covalent inhibitor complexes. Kinase assays compare domain truncations and report the Km values for substrate. THZ531 is presented as a potent and selective inhibitor of CDK12 with nanomolar activity in leukemic cell lines.